Comparison of the seismic performance of a partial mass isolation technique with conventional TMD and base-isolation systems under broad-band and narrow-band excitations. (1st March 2018) - Anajafi, Hamidreza; Medina, Ricardo A.
Highlights: A PMI system is proposed as an alternative to conventional TMD and BI systems. The PMI system provides a building with inherent dynamic vibration suppressors . The PMI effectiveness under broad- and narrow-band excitations is investigated. A PMI system at a low IMR exhibits dynamic characteristics like an equivalent TMD. At a high IMR, the system performs similar to an ideal BI technique. Abstract: In the present study a partial mass isolation (PMI) technique is proposed. This approach, through isolating different portions of masses at different stories, can provide a building with multiple inherent vibration suppressors without the need to add extra masses. Optimization of the PMI system's parameters is conducted for reference structural models with 6, 12, and 20 stories to minimize root-mean-square inter-story drift responses under Kanai-Tajimi filtered Gaussian white noise excitations, while parameter constraints are specified to control isolated components' (ICs) responses. The seismic performance of the PMI technique under excitations with different frequency contents (representing different soil profiles) is compared to that of conventional tuned mass damper (TMD) and base-isolation (BI) systems as baseline configurations. Simulation results indicate that the PMI system with extreme isolated mass ratios of 5% or 90% exhibits dynamic behaviors equivalent to those of an equivalent TMD or an ideal BI systems, respectively. Meanwhile, this technique can resolve some of the inherent difficulties associated with the implementation of TMD (e.g., weight restriction) and BI (e.g., problems due to the superstructure flexibility, overturning moments, and heavy loads) in high-rise buildings.